Dickens and Soundscape: The Old Curiosity Shop - John O. JORDAN (E-REA)
Although critics have devoted considerable attention to the visual dimension of Dickens’s novels, relatively little work has been done on Dickens and sound. This essay takes a sound studies approach to reading The Old Curiosity Shop, arguing that Dickens possessed a powerful auditory imagination that is on full display in this text. The essay gives a brief history of the term “soundscape,” surveys the current state of research on Dickens and sound, proposes a simple taxonomy of Dickensian sound effects, and analyzes various uses to which sound is put in this “noisy” novel.